Trans-alveolar extraction with buccal flap of mandibular second premolar: case report: Ekstraksi trans-alveolar dengan flap bukal dari premolar kedua mandibula: laporan kasus - Abul Fauzi; I Gede Arya Wira Yudha; Eka Prasetyawati (Makassar Dental Journal, 2022)
Many articles have explained the extraction of impacted premolars and canines, but there are still few explanations about li-nguoversion premolar extraction.Trans-alveolar extraction is usually used in cases of impacted teeth or teeth with unfavorable root shape, ankylosis, tooth malposition. Trans-alveolar extraction is atechnique commonly used in dentistry. Various flap op-tions can be used in this technique. In this article it is explained a 30-year-old woman came to the Dental and Oral Hospital of Hasanuddin University with the chief complaint of feeling uncomfortable when eating due to partially growing wisdom teeth and teeth growing towards the tongue. It was performed clinical examination and radiography revealed bilateral linguo-version of the second premolars and impacted third molars. The position of the second premolars was considered difficult be-cause of the obstruction of the mandibular first molars and first premolars. It was conducted transalveolar extraction with a flap in the buccal region under general anesthesia. So, it is concluded that clinical considerations and decisions in achoice of treatment affect the success rate and side effects of treatment. The choice of the buccal flap was carried out taking into account the position of the teeth,the relationship with neighboring teeth, and avoiding injury to the mental nerve that could cause the risk of paraesthesia.